Weighted drownings - An example of augmentation or enhancement of a suicide method. (February 2020) - Stephenson, Lilli; van den Heuvel, Corinna; Byard, Roger W.
Abstract: While planned complex suicides utilize more than one method, on occasion a planned suicide merely involves augmentation of the lethality of the chosen single method. A study was undertaken of augmented suicidal drownings from Forensic Science SA, Adelaide, Australia over a 25-year period (1993–2017). 493 cases (M:F 2.6:1) were found in which death was attributed to drowning. The age range for males was 7mths-93yrs (mean 43.7yrs) and for females 11mths-87yrs (mean 48.2yrs). A subset of 116 suicidal drownings (M:F 1.2:1) had a male age range of 17–86yrs (mean 52.3yrs) and for females 19–68yrs (mean 57.4yrs). 16 individuals in this group (3% of drownings overall) had utilised weights to assist in their submersion (M:F 1.7:1), with an age range for males of 30–84yrs (mean 63.3yrs) and for females 38–81yrs (mean 54.6yrs). The most common weights were bricks, rocks or concrete blocks (N = 7) with weights that were tied to the body most often attached to the neck (N = 7). Augmented drowning by using weights to enhance submersion was not common in this population and was predominantly a technique utilised by older males. Augmentation of a suicide method may be extremely useful support at a death scene to exclude an accident. Highlights: Augmentation refers to suicides where the lethality of the method has been enhanced. 16/116 drowning suicides (3%) had utilised weights to assist in submersion. Augmented drowning with weights was predominantly a technique utilised by older males. Augmentation may be extremely useful support at a death scene to exclude an accident.